JUS NONI UNTUK MENURUNKAN JUMLAH LEUKOSIT DAN NEUTROFIL SEBAGAI INDIKATOR INFLAMASI PADA PAPARAN ASAP ROKOK - Rizana Fajrunni’mah Fajrunni’mah (Jurnal Ilmu dan Teknologi Kesehatan, 2016)
Noni is a functional food can increase antioxidant and anti-inflammatory activities. Cigarette smoke contains oxidants and can cause systemic inflammation, characterized by an increase in the number of leukocyte and neutrophil counts. Leukocytes and neutrophils expressed as an independent marker of prognosis of ischemic cardiovascular disease. The aim of this research was to prove the effect of noni juice to decrease in number of leukocytes and neutrophils in Wistar rats by exposure to cigarette smoke. This research used Pre-posttest control group design with Wistar rats were divided into 2 groups: control (K) and treatment (P) given noni juice 6 ml/day and cigarette smoke exposure for 30 days. The results of this research showed that in number of leukocyte and neutrophil counts in the group giving noni juice is smaller than the control group, with p value 0.016 and p value 0.032. Delivery of noni juice effect on decreasing the number of total leukocyte and neutrophil counts in Wistar rats by exposure to cigarette smoke.